Adoção da viticultura de precisão no Vale dos Vinhedos – Rio Grande do Sul - Silva, Gracieli Manfrin da (2018)
Precision agriculture (PA) has been stimulated by the search for information that minimizes uncertainties in decision making, ensuring a more sustainable management of production systems. In viticulture, the use of PA, named in this case Precision Viticulture (PV), is considered relatively recent. The potential of the use of Precision Viticulture is undeniable, however, becomes relevant diagnose if the technology is being adopted, what factors influence the adoption process, and whether its results are satisfying the perspectives of the viticulturists. The present work sought to make a survey about the adoption of PV tools / techniques by winegrowers from the Vale dos Vinhedos Denomination of Origin region, located in the state of Rio Grande do Sul - Brazil. The research carried out is exploratory and descriptive, making use of qualitative and quantitative analysis techniques. The data were collected through the application of 31 questionnaires to the representatives of wineries and winegrowers in the region. Have been identified only 5 (16,13%) adopters winegrowers of precision viticulture, evidencing the low rate of adoption of the technology in the region. Among the techniques and tools of PV adopted in the Denomination of Origin Vale dos Vinhedos are the georeferencing of the areas, the maps of quality and productivity, the application of fertilizers at varied rates, the georeferenced soil analysis, the application of pesticides at a varied rate, the segmented harvest and the georeferenced monitoring of grape quality parameters. As difficulties in using VP technology, the main ones were the high cost and the difficulty of operationalizing the technologies, the lack of resources to implement the complete system, and financing lines, lack of service providers, as well as the high cost of these. The low rate of adoption of the technology reflects the incipient diffusion of the same among the vintners of the region.